Enhancing Germination and Seedling Growth in Salt Stressed Maize Lines through Chemical Priming - Bolaji U. Olayinka; Abdulbaki S. Abdulbaki; Amudalat R. Lawal; Hameed Alsamadany; Lukman B. Abdulra’uf; Abdulaziz Ayinla; Udo F. Odudu (Maǧallaẗ al-baṣraẗ al-ʻulūm al-zirāʻiyyaẗ)
This study aimed to investigate the tolerance level and the use of primers (H2O, KNO3, ascorbic acid and salicylic acid), in mitigating stress in maize in the newly released cultivars (SWAN-LSR-Y, BR9928-OMR-SR-Y and OMR-LSR-SY). Activities of SOD, APX, CAT and GSH and lipid peroxidation were investigated, to measure the biochemical response of the primed maize seeds. Maize seeds primed with KNO3 and ascorbic acid improved germination and anti-oxidative potential against ROS in ameliorating the salinity stress, while salicylic acid slowed germination. The same trend was followed in the seed vigour index and radicle length of seeds primed with ascorbic acid, which recorded the highest values. The control was observed to have the highest seed vigour index, while seeds primed with salicylic acid showed the least vigour index in the maize seeds.  Increased salinity stress showed adverse effects on all growth parameters. Of the maize cultivars tested, SWAN-LSR-Y showed the most tolerance to salinity stress, in terms of germination. Significant high enzymatic activities and lipid peroxidation were recorded in seeds primed with ascorbic acid and KNO3 show their importance in plant metabolic activities.